(untitled) (Journal of Global Accounting, 2023)
This study assesseS the effect of tax revenue on infrastructural development of Nigeria. Petroleum profit tax, company income tax, value added and custom and excise duties tax were used to proxy tax revenue, while capital expenditure was used to measure economic growth for a period of twenty seven years spanning from 1995 to 2021. Based on the objectives of the study, four hypotheses were formulated. Ex-Post facto research design was adopted. The time series data were obtained from Federal Ministry of Finance, Federal Inland Revenue Services, Central Bank of Nigeria, National Bureau of Statistics and the World Bank Publications. As a preliminary step in testing, the study employed the Augmented Dickey Fully Unit root test to confirm the order of integration of the time series variables. The study employed descriptive statistics and inferential statistics using Pearson correlation and Ordinary Least Square (OLS) regression analysis. The specific findings showed that: Petroleum profit tax has a significant and positive effect on capital expenditure of Nigeria (B= 0.481341; p-value = 0.0060 < 0.05); Company income tax has a significant and positive effect on capital expenditure (B2=0.602013; p-value = 0.0000 0.05); Value Added Tax has a significant and positive effect on capital expenditure (B3= 1.155875; p-value = 0.0000 0.05); Customs and excise duty has a significant and positive effect on capital expenditure (B4= 1.530929; p-value = 0.0000 < 0.05) of Nigeria at 5% level of significance respectively. It was recommended that Government should put in place adequate measure to ensure that revenue generated from tax is effectively utilized to develop and grow the economy through proper infrastructural development.